2020
DOI: 10.1021/acs.est.0c05705
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Chemical Properties, Soil Properties, and Solution pH on Soil–Water Partitioning Coefficients of Per- and Polyfluoroalkyl Substances (PFASs)

Abstract: The aim of this study was to assess the soil–water partitioning behavior of a wider range of per- and polyfluoroalkyl substances (PFASs) onto soils covering diverse soil properties. The PFASs studied include perfluoroalkyl carboxylates (PFCAs), perfluoroalkane sulfonates (PFSAs), fluorotelomer sulfonates (FTSs), nonionic perfluoroalkane sulfonamides (FASAs), cyclic PFAS (PFEtCHxS), per- and polyfluoroalkyl ether acids (GenX, ADONA, 9Cl-PF3ONS), and three aqueous film-forming foam (AFFF)-related zwitterionic PF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
241
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 267 publications
(269 citation statements)
references
References 58 publications
28
241
0
Order By: Relevance
“…It has been well documented that short‐chain PFAS are typically transported through groundwater aquifers at higher velocities than long‐chain PFAS (Gellrich et al, 2012; Guelfo & Higgins, 2013; Higgins & Luthy, 2006; Li et al, 2020; Nguyen et al, 2020). There is not currently enough data to support or refute this hypothesis in the Potomac Aquifer.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been well documented that short‐chain PFAS are typically transported through groundwater aquifers at higher velocities than long‐chain PFAS (Gellrich et al, 2012; Guelfo & Higgins, 2013; Higgins & Luthy, 2006; Li et al, 2020; Nguyen et al, 2020). There is not currently enough data to support or refute this hypothesis in the Potomac Aquifer.…”
Section: Resultsmentioning
confidence: 99%
“…It has been documented that PFBA, a short‐chain PFAS, has similar sorption behavior to its long‐chain congener PFOA, as evidenced by similar log K oc values for these two compounds (Guelfo & Higgins, 2013). However, more recent work found that a suite of soil and sediment properties (carbon content, pH, texture, cation exchange capacity, and soil micropore volume) did a better job of describing subsurface mobility of a variety of PFAS with different chain lengths and charge distributions (Nguyen et al, 2020). Using multiple linear regression analysis, the authors found that long‐chain PFAA sorption was positively related to higher organic carbon content in the soil, negatively related to soil micropore volume, and positively related to silt plus clay content in the soil (Nguyen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The difference in PFAS leachability suggests that soil textural class may play a role and the sandy soils tend to leach out most of the PFAS (65%–99%) they retain. Whether such a trend can be generalized to other soils needs caution, as soil properties could greatly influence the desorption of nonanionic PFAS from soils (Nguyen et al, 2020; Schaefer et al, 2021; Xiao et al, 2019).…”
Section: Resultsmentioning
confidence: 99%